Clinical, Laboratory and Tomographic characteristics associated with obesity and BMI at Hospital admission in adult patients with COVID-19: a cross-sectional study - Mello Neto, Renato Sampaio; Morais, Marcos Henrique de Oliveira; Cronemberger, Pedro Jorge Luz Alves; Xavier, Luan George Lima; Rosal, Marta Alves; Martins, Maria do Carmo de Carvalho e (ABCS Health Sciences, 2022)
Introduction: The pathological status of obesity can influence COVID-19 from its initial clinical presentation, therefore, the identification of clinical and laboratory parameters most affected in the presence of obesity can contribute to improving the treatment of the disease. Objective: To identify the clinical, laboratory, and tomographic characteristics associated with obesity and BMI at t hospital admission in adult patients with COVID-19. Methods: This is a cross-sectional observational study with a total of 315 participants with COVID-19 confirmed by rt-PCR. The participants were divided into non-Obese (n=203) and Obese (n=112). Physical examinations, laboratory tests, and computed tomography of the chest were performed during the first 2 days of hospitalization. Results: Patients with obesity were younger, and they had higher systolic and diastolic blood pressure, higher frequency of alcoholism, fever, cough, and headache, higher ALT, LDH, and red blood cell count (RBC), hemoglobin, hematocrit, and percentage of lymphocytes. Also, they presented a lower value of leukocyte count and Neutrophil/Lymphocyte Ratio (RNL). The parameters positively correlated with BMI were alcoholism, systolic and diastolic blood pressure, fever, cough, sore throat, number of symptoms, ALT in men, LDH, magnesium, RBC, hemoglobin, hematocrit, and percentage of lymphocytes. The parameters negatively correlated with the BMI were: age and RNL. Conclusion: Several parameters were associated with obesity at hospital admission, revealing better than expected results. However, these results should be interpreted with great caution, as there may be some influence of a phenomenon called the Obesity Paradox that can distort the severity and prognosis of the patient.